Comparison of Oral Health Status, Dental Treatment Items, Periodontal Disease between Use of Dental Floss and Interdental Toothbrush Using the 6th Korea National Health and Nutrition Examination Survey - Yu-Rin Kim (Tehran University of Medical Sciences, 2022)
No Abstract